STORYTELLING METHOD TO IMPROVE MOTIVATION IN LEARNING ISLAMIC RELIGIOUS EDUCATION - Idharudin, Abdul Jabar; Nurhasanah, Muwahidah; Rahman; Arsyadi, Isrofil Mirajul (Prodi Pendidikan Agama Islam STAI Darul Falah, 2026)
This research arises from the significance of effective educational approaches in improving students' engagement, especially in Islamic Education at SDIT AL-Hidayah Bogor. This research aims to create and implement storytelling techniques as a learning method that could enhance students' engagement. The research method used is a qualitative case study, with data collection through observation, interviews, and documentation related to the application of storytelling methods in the school. The study results indicate that the storytelling method applied holistically through religious teaching with the subject